Thermal effects and beam parameter variations in electron guns - Khodak, I.V.; Kushnir, V.A.; Mitrochenko, V.V.; Stepin, D.L.; Zhiglo, V.F. (Вопросы атомной науки и техники, 2001)
The paper describes results of research on influence of electrode temperatures and manufacturing tolerance of an electron gun on parameters of an output beam. The Pierce's gun that provides an electron beam with a current of 1.2 A and energy of 25 keV for the S-band technological linac is considered as an example. Numerically calculated parameters of the beam and the temperature distribution in electrodes are presented. It is shown that the acceptable error in a position of electrodes is ±0.1 mm. This value does not fall outside the limit of thermal deformations and technical abilities for manufacturing guns in a laboratory. The scaling to the area of injectors for compact X-band linacs leads to the tolerance of ±0.01 mm that requires introducing fixing and adjustment elements reducing a thermal insulation of the cathode. However, the calculation and experiment showed that such reducing is negligible even for the modern low temperature thermionic cathodes due to a dominant role of the radiation in the heat transfer. This circumstance permits to create the precision intensive compact thermionic electron sources with replacing cathode for the compact linacs.